Efektifitas Penggunaan Media Google Lens Dalam Keterampilan Menerjemah - Nasrullah, M Alaika; Ayu Nafiah , Maya (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
The aim of this research is to determine the effectiveness of Google Lens media on the ability to translate Arabic texts at MAN 3 Banyuwangi. Google lens is an image recognition application. The type of research used is quantitative experimental research. Data collection techniques use observation and tests. This research was conducted using the SPSS program. Data analysis in this research is normality testing and paired sample t-test. The research results show that the correlation between x1 and x2 is 0.836 with a significance of 0.000. So there is a relationship between effectiveness before using Google Lens media and after using it. The calculated t value is greater than the t table (8.586>2.045), there is a significant increase after using Google Lens media. So there is a significant difference between before and after using Google Lens media.